Ekonomik Şiddet ve Kadının Ekonomik Şiddete Karşı Korunması - (:unkn) unknown (My University, 2020)
Bir insan hakları ihlali olarak kadına yönelik şiddetin türü olan ekonomik şiddet, şiddetin gizli yönüdür ve yaşamhakkı ihlaline kadar giden kadına yönelik şiddet eylemlerinde çoğu kez ancak son aşamada diğer temel şiddettürleri olan fiziksel, cinsel ve psikolojik şiddete ek olarak dile getirilmektedir. Halbuki, kadının aile içinde ve dışındamaruz kaldığı ekonomik şiddet, toplumun cinsiyet eşitsizliğiyle, kadının ekonomik bağımsızlığının olmayışıyladoğrudan ilgilidir. Fransız İhtilali ile ortaya çıkan eşitlik düşüncesi, 2. Dünya Savaşı sırası ve sonrası uluslararasıarenanın bir gerekliliği olarak eşitlik; renk, ırk, dil, cinsiyete dayalı ayrımcılığın önlenmesi olarak değerlendirilmiştir.Hukuk devletleri, gerek uluslararası düzenlemeler gerek iç hukuk dolayısıyla kadına yönelik şiddetin her türlüsünüönlemekle yükümlüdür.

Economic violence, a type of violence against women as a human rights violation, is the hidden view of violence. However, in the process leading to violation of the right to life, it is often expressed in addition to other basic forms of violence: physical, sexual and psychological violence. On the other hand, economic violence that women exposed to in their private and family life or public sphere is directly related to the gender inequality of the society and the lack of women’s economic independence. Equality which is the idea of French Revolution, has been reflected as the prevention of discrimination based on colour, race, language and gender as a necessity of the ınternational arena during and after World War II. Constitutional states have the obligation to prevent all forms of violence against women in accordance with international law and domestic law.
Economic Violence and the Protection of Women Against Economic Violence